Effects of soil amendments on bacterial wilt incidences and potato tuber yield across different environments in Malawi - Longwe, K.; Akiniwale, G.; Mwenye, O.; Vugt, D. van; Chiipanthenga, M.; Phiri, A.T. (Elsevier, 2023)
This study investigated the effects of soil amendment on potato yield and incidences of bacterial wilt caused by Ralstonia solanacearum that can cause up to 80% yield loss in potato. The research was conducted at four research stations in Malawi during the 2020/21 and 2021/22 growing seasons, using a randomized complete block design (RCBD) with six treatments: lime, four Calciprill rates (CALC25%, CALC50%, CALC100%, and CALC150%), and NPK fertilizer (control). Data on soil properties, bacterial wilt incidence, and potato tuber yield were collected and analyzed using R programming. Soil fertility was found to be low, with a pH range of 4.4–6.05. Control resulted to significantly higher incidences of bacterial wilt at Kandiyani during 2020/21 (63.6%) and 2021/22 (34.6%) and at Lunyangwa during 2021/22 (20.4%) while lime and all levels of Calciprill led to relative incidence reduction (4%–89%) across sites and season, except CALC25% at Bembeke. Marketable yield showed interaction between amendments and season at Bvumbwe (p = 0.04), highest being 10.02 tha−1 in CALC150% during 2020/21 while non-marketable yield showed interaction at Lunyangwa (p = 0.02) highest being 3.9 tha−1 recorded in CALC150% during 2021/22. A significant negative correlation between bacterial wilt incidences and yield at all sites except Bembeke highlighted the importance of controlling bacterial wilt for yield improvement. The findings suggest that soil amendment through liming is an effective and sustainable approach for managing bacterial wilt and increasing potato yields. Further research on-farm conditions required to ensure the applicability of the findings for different sites.